A systematic review of knowledge management in competency development - Idrus H.M.; Ali N. (Science and Engineering Research Support Society, 2023)
In this paper, we undertake a systematic mapping review to present a review on knowledge management practice and its relation to competency development. It explores the research methodologies used, its findings and results, as well as the research contributions in these two domains. Thirty four articles in various sectors were identified. We concluded that various research methodologies were used for researches on KM and competency development. The paper is intended to practitioners and academics investigating the field of KM and competency development. Specifically, it contributes to direct efforts for future research in knowledge management and competency development. 2019 SERSC.